ANALISIS ORIENTASI PASIEN RAWAT JALAN MELALUI PENDEKATAN WAYFINDING DI RUMAH SAKIT DENGAN MENGGUNAKAN METODE SPACE SYNTAX : ANALYSIS OF OUTPATIENT ORIENTATION THROUGH WAYFINDING APPROACHES IN HOSPITAL USING THE SPACE SYNTAX METHOD - Nadim Arsalan; Andriyanto Wibisono; arsalan, nadim (Universitas Trisakti, 2024)
Analysis of Outpatient Orientation Through Wayfinding Approaches in Hospital Using the Space Syntax Method. The use of wayfinding in hospitals play a crucial role in guiding outpatient orientation. This study aims to assess and evaluate outpatient orientation through the wayfinding approach. It employs a descriptive quantitative method, collecting data through observation and questionnaires filled out by 102 respondents. The data are analyzed using SPSS software to measure patients understanding of orientation in the outpatient area. Additionally, the space syntax method is utilized to analyze two issue regarding spatial legibility in the outpatient area. First orientation and second, the use of wayfinding to enhance effectiveness. Space syntax analysis, conducted using the depthmapX software, aims to identify area causing orientation problems and area with wayfinding issue. The research finding indicate that orientation outpatient capability in the hospital installation exhibits a good level of familiarity, thereby facilitating patient orientation and navigation. However the space syantax results contrasting findings, indicating area that are diffuclt to perceive both visually and in term of distance to rooms, as well as area that serve as activity magnets for patient in the outpatient. Despite patients relatively high understanding of orientation, there are still deficiencies in the use of directional cues. This study provides an evaluation and recommendations to enchance the effectiveness of wayfinding in hospital.